Empowering English Language Learners: Harnessing AI for Enhanced ESL Education (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This paper looks into how studying English as a second language (ESL) might be made easier and more enjoyable by using artificial intelligence (AI). We look at cutting-edge tools like chatbots and smart apps that help kids learn at their own pace. There are challenges to be addressed, though, such making sure that these resources are equal and accessible to all. We also go over how AI can assess your English skills and give you instant feedback so you can get better. We'll also look at how virtual reality and artificial intelligence (AI) can be used to simulate an English-speaking nation while teaching. It's similar like setting out on a language adventure without ever leaving your chamber! Lastly, we offer a sneak peek at potential future developments for AI in ESL, such as utilizing ever-more cutting-edge technology to impart English in ever-more creative ways. Everyone stands to gain from more efficient, interesting, and customized AI-based English language instruction.